Fortuitous Discovery of a Fahr Syndrome in a Psychiatric Environment - DIAGNE, Ibra; DIEYE, Maimouna; SECK, Khadim; NDIAYE-NDONGO, Ndèye Dialé; Sylla , Aida (International Journal of Innovative Research in Medical Science, 2022)
Fahr syndrome is a rare anatomical and clinical entity characterized by bilateral and symmetrical intracerebral calcifications located in the basal ganglia. It is most often associated with disorders of phosphocalcic metabolism and its symptomatology is very heterogeneous ranging from simple headaches to constituted neuropsychiatric disorders. We report the case of a 42-year-old female patient, followed in a psychiatric department since the age of 30 years for a psychotic symptomatology of schizophrenic appearance and well stabilized 8 treatment. On the occasion of a consultation for a psychotic picture associated with repetitive tonicoclonic convulsions and a confusional note, diffuse calcifications of the lenticular nuclei and the cephalic regions of the head of the caudate nuclei were objectified on cerebral computed tomography (CT) and hypocalcemia on biology. These anatomic-clinical and biological data allowed us to retain the Fahr syndrome. This clinical observation shows the importance of suspecting this syndrome in the presence of an abruptly changing chronic psychiatric picture associated with neurological signs in order to adapt the global management. A correction of the phosphocalcic metabolism disorders often leads to a clear improvement.